Pecan: A potential fruit crop for Indian Himalayas - Yadav, Ram Prakash; Bisht, Jaideep Kumar; Joshi, Kushagra; Meena, Vijay Singh; Mondal, Tilak; Parihar, Manoj; Choudhary, Mahipal; Kant, L (Indian Horticulture, 2024)
Globally, in the last decade, production of nut fruit crops have grown at a steady pace reaching ~5.4 million metric tonnes in 2022-23 according to International Nut and Dried Fruit Council (INC). United States of America was the top tree nut producer with 40% share, whereas India contributed only 3.5%. Pecan nut contributed 3% of the total tree nut production and in the last half decade, pecangrowing trends displayed significant linear increments of 16,465 MT/year. In terms of estimated global tree nut consumption in 2021, almonds (31%) and walnuts (21%) accounted for half the total, while pecans made up 3%. Supply value of tree nut crops increased over the previous 10 years including pecans from $0.92 billion in 2012-13 to 2.05 billion in 2022-23.